Sunnah Prayer And Sunnah Fasting On Increasing The Character Value Of Physical Education In Boarding Boards - Eko Yogaswara; Adang Sudrazat; Anggi Setia Lengkana (JUARA : Jurnal Olahraga, 2022)
Pesantren is an educational institution where to educate and gain knowledge, not only religious knowledge but must be able to form character based on the character values ​​of the Ministry of National Education. The research that the researcher conducted aims to analyze the activities of sunnah worship to increase character values ​​in the Shalafi Islamic Boarding School environment. This research was conducted with descriptive research through a quantitative approach. The results of data processing and analysis show that sunnah prayers and sunnah fasting, on increasing character values ​​in physical education with the results it can be accepted that there is a significant effect. Although based on the calculation of determination, it is known that the increase of 21.2% and 78.8% is influenced by other factors not examined.